The change of Astigmatism before and after phacoemulsification cataract surgery with temporal incision in senile cataract patients at RSUP Fatmawati year 2015 – 2016 - Maralaut, Azhardin; Farida, Nida; Sari, Nurmila (International Journal of Human and Health Sciences (IJHHS), 2020)
Azhardin Maralaut Siregar. Medical Studies and Medical Eduaction Program. The change of Astigmatism Before and After Phacoemulsification Cataract Surgery with Temporal Incision in Senile Cataract Patients at RSUP Fatmawati year 2015-2016. Background: Cataract is a common disease in the elderly. Treatment of cataracts to date is by surgery, one of them with phacoemulsification technique, which is considered to have the best results because it gives the very small effect of change in astigmatism. Some of the factors that cause astigmatism change are the surgical techniques as well as the large and the location of the incision. Objective: To know the change of astigmatism in senile cataract patient before and after surgery with phacoemulsification technique at RSUP Fatmawati. Method: This research uses cross sectional design conducted in February 2017 until August 2017 at RSUP Fatmawati. The study used secondary data taken from a medical record of senile cataract patients who had undergone phacoemulsification technique surgery performed by one ophthalmologist in January 2015 to December 2016. Results: Respondents numbered 52 eyes from 52 patients aged ≥50 years. Analyzed using kolmogorov-smirnov test, it was found that the astigmatism change was not significant in the first week after surgery with p value 0.319, the insignificant astigmatism change in the third week after surgery with p value 0,505, the insignificant astigmatism change in the sixth week after surgery of astigmatism before operation with p value 0.311. But there was an increasing number of astigmatism patients from 32 (65%) to 39 patients (75%). Conclusions: There was an insignificant astigmatism change in the first, third and sixth weeks after phacoemulsification surgery of senile cataracts. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 55-61